Symptom Burden’s Associated Factors among Hemodialysis Patients - Early Octavia Limbong; Tuti Pahria; Sri Hartati Pratiwi (Jurnal Keperawatan Padjadjaran, 2020)
Many patients with chronic kidney disease undergoing hemodialysis (CKD-HD) had a high symptom burden, which can worsen their health conditions and quality of life. The known factors associated to symptom burden were age, gender, hemodialysis (HD) session duration, post dialysis recovery time, hemoglobin level, nutrition status, physical activity, depression level and social support. The aim of this study was to analyze the most dominant factor associated to symptom burden among CKD-HD patients. Using a cross-sectional design, a convenience sample of eighty-five respondents were recruited from HD unit at Adventist Bandung Hospital, who underwent HD > 3 months, HD frequency 2-3 times a week, aged ≥ 18 years, able to communicate and speak Indonesian. Data were retrieved via seven self-reported questionnaires and health records, and the symptom burden was assessed using the validated Indonesian version of the CKD-Symptom Burden Index. The data was analysed with Spearman correlation test, Chi square test, and multivariate logistic regression. Based on quartile category, most of the respondents (50.6%) had a high symptom burden (33.56±12.23). The factors significantly associated to symptom burden were age (p=0.015), post-dialysis recovery time (p=0.007) and depression level (p=0.000). In the final model, duration of HD session (OR=5.27, 95% CI 1.50-18.49) and depression level (OR=8.84, 95% CI 2.57-30.36) were the factors associated to high symptom burden. Depression level was the most dominant factor associated to high symptom burden. CKD-HD patients with depression are more at risk of experiencing a high symptom burden. Thus, symptom management may consider to modify depression level factor by screening for depression, providing assistance and nursing interventions, or developing depression-related interventions to reduce symptom burden in CKD-HD patients.